Konstruksi sosial pembagian hak waris anak angkat masyarakat muslim Samin Dusun Jepang Margomulyo Bojonegoro - Mujahidin, Moh Iqbal; Huda, Miftahul (Asy-Syari’ah : Jurnal Hukum Islam, 2024)
The enforcement of Islamic law in Indonesia society is frequently still questionable in practice. The reason is utilization of customary law is still often in indonesia's society, especially in the case relating to inheritance law. The Moslem Samin community of Jepang Hamlet Margomulyo Bojonegoro is one of the community entities that still upholds its customary teachings, including in determining the distribution of inheritance to adopted children. This study aims to describe: (1) the law used in the distribution of the inheritance of adopted children by the Samin's Moslem community in Jepang Hamlet, and (2) Social construction of the Samin community in distributing inheritance to adopted children. This research is a type of field research, which uses primary data in the form of observation and interview results, by choosing a research location in Jepang Hamlet, Margomulyo Bojonegoro. The respondents are the Samin's Moslem community, community leaders and traditional leaders. The approach used in this research is an anthropological historical sociological approach, to fully capture the application of the law of the Samin muslim community, especially in relation to the inheritance rights of adopted children. The findings obtained in this study are; first, in determining the heirs, the Samin Muslim community establishes adopted children as the legal heirs of the deceased parents. Second, the Samin Muslim community prefers to use customary law rather than Islamic law. this is due to five factors, namely the concept of justice, the concept of equality, the complexity of Islamic law, the absence of religious leaders and the absence of religious institutions. Third, the community and Samin leaders of Jepang Hamlet Margomulyo Bojonegoro agree that adopted children have the right to the property of their adoptive parents